2017
DOI: 10.1038/s41598-017-12561-7
|View full text |Cite
|
Sign up to set email alerts
|

Premature contractions of the bladder are suppressed by interactions between TRPV4 and SK3 channels in murine detrusor PDGFRα+ cells

Abstract: During filling, urinary bladder volume increases dramatically with little change in pressure. This is accomplished by suppressing contractions of the detrusor muscle that lines the bladder wall. Mechanisms responsible for regulating detrusor contraction during filling are poorly understood. Here we describe a novel pathway to stabilize detrusor excitability involving platelet-derived growth factor receptor-α positive (PDGFRα+) interstitial cells. PDGFRα+ cells express small conductance Ca2+-activated K+ (SK) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 44 publications
1
29
0
Order By: Relevance
“…Of all the TRPs, the TRPV4 seems to be the most implicated in bladder function as sensor of stretch and regulator of bladder filling 34 . The presence of TRPV4 was detected in rodents' (mice, rats, guinea-pigs) urothelium, DSM, vascular endothelium and interstitial cells [37][38][39][40][41] as well as in human urothelium 47 . Trpv4-knockout mice demonstrate aberrant voiding pattern and stretch-evoked ATP release from urothelium 37 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of all the TRPs, the TRPV4 seems to be the most implicated in bladder function as sensor of stretch and regulator of bladder filling 34 . The presence of TRPV4 was detected in rodents' (mice, rats, guinea-pigs) urothelium, DSM, vascular endothelium and interstitial cells [37][38][39][40][41] as well as in human urothelium 47 . Trpv4-knockout mice demonstrate aberrant voiding pattern and stretch-evoked ATP release from urothelium 37 .…”
Section: Discussionmentioning
confidence: 99%
“…Nowadays, however, this view has evolved to a concept of polymodal ionotropic receptor activated by multiplicity of stimuli, ranging from hypotonicity to heat and acidic pH 34 . TRPV4 is one of the most implicated channels in bladder function mostly as urothelial stretch sensor and mediator of stretch-evoked ATP release [34][35][36] , with possible species-specific expression and function in other bladder tissues (DSM, interstitial cells, vascular endothelium) as well [37][38][39][40][41] .…”
Section: Efs-evoked Contractions Electric Field Stimulation (Efs) Ofmentioning
confidence: 99%
“…While it has been suggested that these interstitial cells inhibit UBSM excitability through interactions between small‐conductance K + channels and TRPV4 channels (Lee et al . ; ), it is possible that they may act as an excitatory influence on the bladder smooth muscle. K V 7 currents have been recorded from guinea pig interstitial cells, and evidence suggests K V 7 channels are integral to the maintenance of interstitial cell resting membrane potential and excitability (Anderson et al .…”
Section: Discussionmentioning
confidence: 99%
“…Distention of the posterior urethra by the seminal fluid bolus stimulates a reflex arc that triggers expulsion 7 . Wall mechanoceptors (ie, afferent nerve processes) are found near to and within the stratified urothelium, interstitial cells, and in and around the smooth muscle layer in the lower urinary tract 28,34–40 . Both neuronal and non‐neuronal cell types respond to the changes in wall tension that accompany fluid flow or retention and have been reported to be mechanosensitive, including those associated with the terminals of sensory neurons that innervate the urethral wall 28 .…”
Section: Discussionmentioning
confidence: 99%
“…7 Wall mechanoceptors (ie, afferent nerve processes) are found near to and within the stratified urothelium, interstitial cells, and in and around the smooth muscle layer in the lower urinary tract. 28,[34][35][36][37][38][39][40] Both neuronal and non-neuronal cell types respond to the changes in wall tension that accompany fluid flow or retention and have been reported to be mechanosensitive, including those associated with the terminals of sensory neurons that innervate the urethral wall. 28 For example, a stretch-activated channel, PIEZO1, functions as a mechanosensor that triggers responses to changes in the tension of the wall.…”
Section: Discussionmentioning
confidence: 99%